Physical rehabilitation of disabled people who suffered a cerebrovascular accident (late period) - Khrystova T.E (Kharkov National Pedagogical University, 2012)
There are the results of putting into practice a comprehensive program for physically handicapped people in the late period of stroke. The study included 39 disabled people with brain attack effects - 10 men (25.6%) and 29 women (74.4%) aged 24-68 years. A program of physical rehabilitation included physical therapy, massage, dosed walking, tempering, biostimulation (Shuboshi device), diet therapy. It was determined that using the mentioned methods for recovering disabled people leads to increasing the circles on limb segments in healthy (up to 14%) and in the caused (up to 11%) sides. The putting into practice a comprehensive rehabilitation program also leads to improving of hand dynamometry indices (men 24% and women - 9%), to boosting static muscle endurance of shoulder structure in men to 88%, women to 105% on the side of hemiparesis; to forming optimal locomotion, thus maintaining any rate of walking 1 hour- 46.3% of patients, 30-45 minutes - 38.4%; to stable compensation of orthostaticus violations in 31 individuals (79.6%).